1998
DOI: 10.1038/30006
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhi uses CFTR to enter intestinal epithelial cells

Abstract: Homozygous mutations of the cystic fibrosis transmembrane conductance regulator (CFTR) cause cystic fibrosis (CF). In the heterozygous state, increased resistance to infectious diseases may maintain mutant CFTR alleles at high levels in selected populations. Here we investigate whether typhoid fever could be one such disease. The disease is initiated when Salmonella typhi enters gastrointestinal epithelial cells for submucosal translocation. We found that S. typhi, but not the related murine pathogen S. typhim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
231
0
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(237 citation statements)
references
References 21 publications
2
231
0
4
Order By: Relevance
“…Convincing demonstrations of overdominance have been provided for a small number of human genes including glucose-6-phosphate dehydrogenase, 53 hemoglobin-b, 54 the cystic fibrosis transmembrane conductance regulator, 55 a member of the interleukin-1 family (IL1F5) 48 and the Kidd blood group antigen gene; 23 in all these cases, the responsible selective pressure is thought to be accounted for by an infectious agent. 56 Our data indicate that balancing selection maintaining two major lineages at the MEFV ex5ÀUTR region is likely due to overdominance in Caucasians and AS; indeed, a number of heterozygotes higher than expected is observed in these populations and in the case of EAs the deviation we observed for MEFV is the most extreme in the set of NIEHS genes (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Convincing demonstrations of overdominance have been provided for a small number of human genes including glucose-6-phosphate dehydrogenase, 53 hemoglobin-b, 54 the cystic fibrosis transmembrane conductance regulator, 55 a member of the interleukin-1 family (IL1F5) 48 and the Kidd blood group antigen gene; 23 in all these cases, the responsible selective pressure is thought to be accounted for by an infectious agent. 56 Our data indicate that balancing selection maintaining two major lineages at the MEFV ex5ÀUTR region is likely due to overdominance in Caucasians and AS; indeed, a number of heterozygotes higher than expected is observed in these populations and in the case of EAs the deviation we observed for MEFV is the most extreme in the set of NIEHS genes (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, the slight overabundance of polymorphic replacement mutations in NBD1 may be due to Darwinian natural selection. For example, Pier et al (1998) suggested that there may be a selective advantage for F508 in terms of an increased resistance to infection by Salmonella typhi. Further, it has been suggested that individuals heterozygous for F508 may have a generalized resistance to diarrheal diseases (Baxter et al 1988;Guggino, 1999) or reduced incidence of bronchial asthma (Schroeder et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The mutation ΔF508 in Cystic fibrosis also has a high incidence in the Ashkenazi population [52]. This mutation in another ATP transporter was associated with protection against cholera and typhoid fever [53,54]. However, it has yet to be determined if the high prevalence of the 3435C>T SNP has a heterozygote advantage in these diseases.…”
Section: Discussionmentioning
confidence: 99%